Cholesterol metabolism in the regulation of inflammatory responses - Bauer, Rebekka; Brüne, Bernhard; Schmid, Tobias (Frontiers in Pharmacology, 2023)
The importance of biologically active lipid mediators, such as prostanoids, leukotrienes, and specialized pro-resolving mediators, in the regulation of inflammation is well established. While the relevance of cholesterol in the context of atherosclerosis is also widely accepted, the role of cholesterol and its biosynthetic precursors on inflammatory processes is less comprehensively described. In the present mini-review, we summarize the current understanding of the inflammation-regulatory properties of cholesterol and relevant biosynthetic intermediates taking into account the implications of different subcellular distributions. Finally, we discuss the inflammation-regulatory effect of cholesterol homeostasis in the context of SARS-CoV-2 infections.